Analisis Unsur Budaya Dalam Tradisi Sabumi Babarit di Desa Citangtu Kecamatan Kuningan Kabupaten Kuningan - Julianti, Delia; Nuraeni, Leni (Fakultas Ilmu Budaya Universitas Diponegoro, 2024)
Indonesia has various cultures and traditions that are still maintained. From these various traditions, there are different elements and values, each of which has unique characteristics. This cultural diversity is found in various corners of Indonesia, such as what can be found in the eastern part of West Java, namely in Kuningan Regency. Kuningan has various traditions, cultures and customs that are still maintained. You can find a tradition that is still routinely carried out in Kuningan Regency, specifically in Citangtu Village, namely Talahab Hamlet, where the Sabumi Babarit tradition is still carried out. This article aims to find out the reasons why this tradition is still carried out and what cultural elements are included in this tradition. This study uses a qualitative approach and research on this cultural element uses Koetjaraningrat theory. The results obtained from this research are that there are 4 processions carrying out the sabumi babarit tradition, namely; 1) Hajat kekah, 2) Sura porridge, 3) Sabumi babarit, 4) Golewang. It is hoped that the results obtained will be useful for all readers.This is a description of the research that contains the formulation of the problem, objectives, methods, theoretical and literature reviews, and general results. If using Indonesian language, it must be adjusted to the latest Indonesian language rules and spelling. Composed in 150-200 words. Using Times New Roman font, 11pt size, 1 space, and italicized. Keywords: sabumi babarit, traditions, cultural elements